Experiments on deformation behaviour of functionally graded NiTi structures - Bashir S. Shariat; Qinglin Meng; Abdus S. Mahmud; Zhigang Wu; Reza Bakhtiari; Junsong Zhang; Fakhrodin Motazedian; Hong Yang; Gerard Rio; Tae-hyun Nam; Yinong Liu (Data in Brief, 2017)
Functionally graded NiTi structures benefit from the combination of the smart properties of NiTi and those of functionally graded structures. This article provides experimental data for thermomechanical deformation behaviour of microstructurally graded, compositionally graded and geometrically graded NiTi alloy components, related to the research article entitled “Functionally graded shape memory alloys: design, fabrication and experimental evaluation” (Shariat et al., 2017) [1]. Stress–strain variation of microstructurally graded NiTi wires is presented at different heat treatment conditions and testing temperatures. The complex 4-way shape memory behaviour of a compositionally graded NiTi strip during one complete thermal cycle is demonstrated. The effects of geometrical design on pseudoelastic behaviour of geometrically graded NiTi plates over tensile loading cycles are presented on the stress–strain diagrams. Keywords: Shape memory alloy (SMA), NiTi, Martensitic transformation, Functionally graded material (FGM), Pseudoelasticity, Heat treatment